Highly Reflective Dielectric Back Reflector for Improved Efficiency of Tandem Thin-Film Solar Cells - Chog Barugkin; Ulrich W. Paetzold; Kylie R. Catchpole; Angelika Basch; Reinhard Carius (International Journal of Photoenergy)
We report on the prototyping and development of a highly reflective dielectric back reflector for application in thin-film solar cells. The back reflector is fabricated by Snow Globe Coating (SGC), an innovative, simple, and cheap process to deposit a uniform layer of TiO2 particles which shows remarkably high reflectance over a broad spectrum (average reflectance of 99% from 500 nm to 1100 nm). We apply the highly reflective back reflector to tandem thin-film silicon solar cells and compare its performance with conventional ZnO:Al/Ag reflector. By using SGC back reflector, an enhancement of 0.5 mA/cm2 in external quantum efficiency of the bottom solar cell and an absolute value of 0.2% enhancement in overall power conversion efficiency are achieved. We also show that the increase in power conversion efficiency is due to the reduction of parasitic absorption at the back contact; that is, the use of the dielectric reflector avoids plasmonic losses at the reference ZnO:Al/Ag back reflector. The Snow Globe Coating process is compatible with other types of solar cells such as crystalline silicon, III–V, and organic photovoltaics. Due to its cost effectiveness, stability, and excellent reflectivity above a wavelength of 400 nm, it has high potential to be applied in industry.